FINANCIAL STABILITY OF LOCAL GOVERNMENT UNITS – LEGAL AND ECONOMIC APPROACH - Cilak, Małgorzata (Copernican Journal of Finance & Accounting, 2019)
The legislator introduced solutions conducive to the financial stability of local government units in the form of Articles 242 and 243 of the Public Finance Act of 2009. They force the reduction of deficit in the so-called current part of the local government budget and limit the amount of funds allocated for the repayment of financial liabilities. The aim of this article is to examine the impact of the obligation to comply with these regulations on the finances of local government units. The article will examine the content of both regulations and statistical data from the Reports on Budget Execution by Local Government Units, provided by the National Council of Regional Chambers of Audit. The summary will present a conclusion that Articles 242 and 243 of the Public Finance Act have a significant impact on the financial management of local governments, obliging them to maintain appropriate proportions between the amounts of income and current expenditure. However, the legal structure of both rules provides for certain exceptions to their absolute observance, which weakens their impact on the finances of local governments.